PENINGKATAN HASIL BELAJAR SPRINT MELALUI METODE RESIPROKAL SISWA KELAS IV SD NEGERI 68 PONTIANAK - Hiqbal, Muhammad Noor; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study is inspired by the problems on the low achievement of students’ sprint learning, particularly in Public Elementary School 68 West Pontianak. The purpose of this study is to investigate the improvement of students’ achievement on sprint learning through reciprocal method. This research method uses classroom action receach.The participants chosen in this study were the 40 fourth-grade students of Public Elementary School 68 West Pontianak in academic year 2018/2019. The data analysis used in this study is descriptive analysis. The results of pre-cycle research in IV-B class showed that the lowest score was 20 and the highest score was 80 with an average score of 53.75. For cycle 1, the lowest score is 60 and the highest score is 100 with an average score of 77.00. For cycle 2, the lowest score is 80 and the highest score is 100 with an average score of 87.50. In pre- cycle, there were only 7 (17.5%) out of 40 students achieved the score standard. Meanwhile, the number of students who reached the score standard in cycle 1 was 34 (85%) out of 40 students and finally in cycle 2, all students succeeded to reach the score standard. Keywords: Reciprocal, Sprint, Learning Results.